Telehealth for amyotrophic lateral sclerosis in a multidisciplinary service in a Brazilian reference center - Fidelix, Emanuela Coriolano; Santana, Glauciane Costa; Barros, Daniele Montenegro da Silva; Dourado Junior, Mário Emílio Teixeira (Arquivos de Neuro-Psiquiatria, 2023)
Background Telehealth has been used in the treatment of different diseases, and it has been shown to provide benefits for patients with amyotrophic lateral sclerosis (ALS). Due to the social distancing measures put into effect during the coronavirus disease 2019 (COVID-19) pandemic, there was an urgent need for telehealth to ensure the provision of healthcare.Objective To evaluate the feasibility of telehealth for the provision of multidisciplinary ALS care, and to assess its acceptability among patients and caregivers.Methods We conducted a retrospective cohort study in which multidisciplinary evaluations were performed using the Teleconsulta platform. The patients included had ALS and at least one in-person clinical evaluation. The patients and the caregivers answered satisfaction questionnaires.Results The sample was composed of 46 patients, 32 male and 14 female subjects. The average distance from their residences to the reference services was of 115 km. Respiratory adjustment was the most addressed topic.Conclusion The strategy is viable and well accepted in terms of satisfaction. It was even more positive for patients in advanced stages of the disease or for those living far from the referral center.
Keywords: Amyotrophic Lateral Sclerosis; Motor Neuron Disease; Telemedicine